Influence of crop management practices on late sown toria (Brassica campestries var. toria) under rainfed rice-fallow situation of Assam - Bebi Gogoi,; K Kurmi,; K Thakuria,; NJ Ojha,; S Dutta, (Journal of Oilseed Brassica, 2026)
A field experiment was conducted under rainfed condition during the rabi season of the year 2014-2015 and2015-2016 at the Instructional-cum-Research farm, Assam Agricultural University, Jorhat, India to study theperformance of recently developed late sown toria var. JT-90-1 (Jeuti) under different dates of sowing, seedrates and method of sowing in medium land rice-fallow situation. The experiment was conducted in split plotdesign with three replications keeping the dates of sowing in the main plots and combination of seed rates andmethod of sowing in the sub plots. The treatments consisted of 4 sowing dates, viz. 1st, 8th, 15th and 22ndDecember; 3 seed rates, viz. 6, 8 and 10 kg/ha and 2 methods of sowing viz. line sowing at 25 cm apart andbroadcasting. The highest seed yield of 724.3 and 742.1 kg/ha, stover yield of 2268.4 and 2296.5 kg/ha andseed oil content of 35.1 and 35.2% were recorded in 1st December sown crop which were significantlyhigher over other dates of sowing in first and second year, respectively. The extent of decrease in seed yieldwas 9.2 to 34.6% and 6.8 to 32.6% for 7 and 21 days delay in sowing from 1st December (D1) during the firstand second year, respectively. The seed rate of 10 kg/ha (S3) recorded significantly higher yield of seed,stover, seed oil content over that of 6 and 8 kg/ha. In case of sowing method line sowing was found to bebetter than broadcasting in all growth and yield attributing characters. The crop recorded highest gross return(50,223.4 /ha), net return (33,013.4 /ha) and benefit-cost ratio (2.9) when sown on 1st December with seedrate of 10 kg/ha in lines made at 25 cm apart.